Fat oxidation rates and cardiorespiratory responses during exercise in different subject populations with post-acute sequelae of SARS-CoV-2 infection: a comparison with normative percentile values - Meloni, Andrea; Codella, Roberto; Gotti, Daniel; Di Gennaro, Simone; Luzi, Livio; Filipas, Luca (Frontiers in Physiology, 2023)
INTRODUCTION: Post-acute sequelae of SARS-CoV-2 infection (PASC) presents a spectrum of symptoms following acute COVID-19, with exercise intolerance being a prevalent manifestation likely linked to disrupted oxygen metabolism and mitochondrial function. This study aims to assess maximal fat oxidation (MFO) and exercise intensity at MFO (FATmax) in distinct PASC subject groups and compare these findings with normative data. METHODS: Eight male subjects with PASC were involved in this study. The participants were divided in two groups: "endurance-trained" subjects (V ̇O2max > 55 ml/min/kg) and "recreationallyactive" subjects (V ̇O2max < 55 ml/min/kg). Each subject performed a graded exercise test until maximal oxygen consumption (V ̇O2max) to measure fat oxidation. Subsequently, Maximal Fat Oxidation (MFO) was assessed and FATmax calculated as the ratio between V ̇O2 at MFO and V ̇O2max. RESULTS: MFO and FATmax of "endurance-trained" subjects were 0.85, 0.89, 0.71 and 0.42, and 68%, 69%, 64% and 53%, respectively. 3 out of 4 subjects showed MFO and FATmax values placed both over the 80 th percentile of normative data. MFO and FATmax of "recreationally-active" subjects were 0.34, 0.27, 0.35 and 0.38, and 47%, 39%, 43% and 41%, respectively. All MFO and FATmax values of those subjects placed below the 20 th percentile or between the 20 th and 40 th percentile. DISCUSSION: Significant differences in MFO and FATmax values between 'endurance-trained' and "recreationally-active" subjects suggest that specific endurance training, rather than simply an active lifestyle, may provide protective effects against alterations in mitochondrial function during exercise in subjects with PASC.